Wathint" Umfazi, Wathint" Imbokodo, Uzakufa [You Strike a Woman, You Strike a Rock, You Will Die]: Dinah and Tamar as rape protestors - Ramantswana, Hulisani (HTS teologiese studies, 2019)
This article reflects on two rape stories, namely, the rape of Dinah and the rape of Tamar. In the two rape stories, the male figures are portrayed as heroes – the defenders of the rape victims. However, this article uses the isiZulu saying ‘Wathint’umfazi, wathint’ imbokodo, uzakufa’ to foreground the role of the rape victims as the unsung heroines in the stories. Thus, the paper presents Dinah and Tamar as heroines, who represent the demand for justice in the face of the violation of female bodies in society. It is the woman’s voice of protest that should be heard in each of the rape story crying out, ‘My life matters!’